Nematomorpha - poorly known parasites of invertebrates - Łapkiewicz, Katarzyna; Cichy, Anna (Ecological Questions, 2024)
Nematomorpha, also known as ‘horsehair worms’, is a poorly known group of animals that parasitize as larvae both, invertebrates and, less frequently vertebrates. There are approximately 360 species within this phylum, and previously, they were incorrectly classified as representatives of nematodes due to morphological similarity. Nematomorpha are cosmopolitan, found in fresh and salt water, and on land, usually in humid habitats. Their life cycles are simple or complex and usually associated with the phenomenon of ‘parasitic manipulation’ of the host. This term refers to parasites that can take control of their host’s body and behaviour. These efforts mainly lead to the host’s death in the name of parasites’ survival. The level of knowledge about Nematomorpha is insufficient, as is the role of these behaviour-altering parasites in the ecosystem. This is mainly due to their relatively low species representativeness and a secretive lifestyle in which, alongside free-living adults, there are parasitic larvae. The aim of this article is a review of the literature on ‘horsehair worms’ and an attempt to determine further directions of research on this systematic group.